2022
DOI: 10.1073/pnas.2110158119
|View full text |Cite
|
Sign up to set email alerts
|

A functional division of Drosophila sweet taste neurons that is value-based and task-specific

Abstract: Sucrose is an attractive feeding substance and a positive reinforcer for Drosophila. But Drosophila females have been shown to robustly reject a sucrose-containing option for egg-laying when given a choice between a plain and a sucrose-containing option in specific contexts. How the sweet taste system of Drosophila promotes context-dependent devaluation of an egg-laying option that contains sucrose, an otherwise highly appetitive tastant, is unknown. Here, we report that devaluation of sweetness/sucrose for eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…The optogenetically induced avoidance may therefore result from unnatural levels or patterns of sugar neuron activation, which may cause compensatory changes in the downstream circuit. However, a recent study showed that activating different subsets of sugar neurons at the same relatively low intensity (6.8 µW/mm 2 ) elicited different effects on positional preference, including avoidance (Chen et al, 2022). Avoidance of sugar may be relevant during specific behaviors such as egg-laying, as flies avoid laying eggs on sugar in some contexts (Yang et al, 2008; Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The optogenetically induced avoidance may therefore result from unnatural levels or patterns of sugar neuron activation, which may cause compensatory changes in the downstream circuit. However, a recent study showed that activating different subsets of sugar neurons at the same relatively low intensity (6.8 µW/mm 2 ) elicited different effects on positional preference, including avoidance (Chen et al, 2022). Avoidance of sugar may be relevant during specific behaviors such as egg-laying, as flies avoid laying eggs on sugar in some contexts (Yang et al, 2008; Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We have not performed a similar set of experiments for sugar neurons, and it is possible that they would show a greater degree of organ-specific behavioral regulation. Indeed, several studies have shown that sugar neurons in different organs have different behavioral effects (Thoma et al, 2016; Murata et al, 2017; Chen et al, 2021; Chen et al, 2022). Perhaps organ-specific roles for appetitive tastes are needed to generate the appropriate sequence of motor subprograms during feeding, whereas aversive behaviors do not follow an organ-specific sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We cannot exclude that more subtle differences in the numbers of func<onally-dis<nct sugar-GRN subtypes exist between species. Indeed, different sub-popula<ons of sugar-GRNs in D. melanogaster exert opposite effects on oviposi<on behavior, with GRNs on the legs inhibi<ng oviposi<on while GRNs on the proboscis promo<ng oviposi<on in a specific context 37 . Interes<ngly, we observed a reduc<on of sugar-GRNs in tarsal segments 2, 3 and 4 of the D. suzukii foreleg compared to D. melanogaster, raising the possibility that disappearance of specific neuronal subtypes could have relieved inhibitory sugar inputs onto CNS oviposi<on circuits in this species.…”
Section: Discussionmentioning
confidence: 99%